Evaluation of the nutrient contents of palm kernel cake fermented by microbial cocktails as a potential feedstuff for poultry - Pasaribu, T.; Laconi, E.B.; Kompiang, I.P. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The aims of this research were to improve the nutritive value of palm kernel cake by fermentation technology using Bacillus amyloliquefacien, Trichoderma harzianum and cocktail microbes (combination of Bacillus amyloliquefacien and Trichoderma harzianum). Data were analyzed using Completely Randomized Design Factorial, with experiments consisting of types of microbes (B. amyloliquefaciens, T. harzianum, microbial cocktail) as treatment and incubation time (0, 3, 5, and 7 days). Parameters were crude protein and crude fiber for all treatments, and the lowest fiber analysis would continue with NDF, ADF, crude fat, and amino acids. Result showed that the three of microbes grew on palm kernel meal in third incubation and grew on and in the substrate at 7 days. microbial cocktails increased protein and reduced crude fiber better than B. amyloliquefacien and T. harzianum on palm kernel cake fermentation technology. Cocktail microbes enhanced amino acids such as methionine, arginine, and glutamic acid, also neutral detergent fiber but reduced ADF and hemicellulose. It was concluded that the palm kernel cake fermented with microbial cocktails can reduced crude fiber and increase crude protein with an incubation period of 7 days.